Genomic analysis of serologically untypable human enteroviruses in Taiwan - Chien, Yeh-Sheng (J Biomed Sci, 2019)
BACKGROUND: Human enteroviruses contain over 100 serotypes. We have routinely conducted enterovirus surveillance in northern Taiwan; but about 10% of isolates could not be serotyped using traditional assays. Next-generation sequencing (NGS) is a powerful tool for genome sequencing. METHODS: In this study, we established an NGS platform to conduct genome sequencing for the serologically untypable enterovirus isolates. RESULTS: Among 130 serologically untypable isolates, 121 (93%) of them were classified into 29 serotypes using CODEHOP (COnsensus-DEgenerate Hybrid Oligonucleotide Primer)-based RT-PCR to amplify VP1 genes (VP1-CODEHOP). We further selected 52 samples for NGS and identified 59 genome sequences from 51 samples, including 8 samples containing two virus genomes. We also detected 23 genome variants (nucleotide identity < 90% compared with genome sequences in the public domain) which were potential genetic recombination, including 9 inter-serotype recombinants and 14 strains with unknown sources of recombination. CONCLUSIONS: We successfully integrated VP1-CODEHOP and NGS techniques to conduct genomic analysis of serologically untypable enteroviruses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12929-019-0541-x) contains supplementary material, which is available to authorized users.